Transient Depletion of Foxp3+ Regulatory T Cells Selectively Promotes Aggressive β Cell Autoimmunity in Genetically Susceptible DEREG Mice - Watts, Deepika; Janßen, Marthe; Jaykar, Mangesh; Palmucci, Francesco; Weigelt, Marc; Petzold, Cathleen; Hommel, Angela; Sparwasser, Tim; Bonifacio, Ezio; Kretschmer, Karsten (Frontiers in Immunology, 2021)
Type 1 diabetes (T1D) represents a hallmark of the fatal multiorgan autoimmune syndrome affecting humans with abrogated Foxp3+ regulatory T (Treg) cell function due to Foxp3 gene mutations, but whether the loss of Foxp3+ Treg cell activity is indeed sufficient to promote  cell autoimmunity requires further scrutiny. As opposed to human Treg cell deficiency,  cell autoimmunity has not been observed in none-autoimmune-prone mice with constitutive Foxp3 deficiency or after diphtheria toxin receptor (DTR)-mediated ablation of Foxp3+ Treg cells. In the spontaneous nonobese diabetic (NOD) mouse model of T1D, constitutive Foxp3 deficiency did not result in invasive insulitis and hyperglycemia, and previous studies on Foxp3+ Treg cell ablation focused on Foxp3DTR NOD mice, in which expression of a transgenic BDC2.5 T cell receptor (TCR) restricted the CD4+ TCR repertoire to a single diabetogenic specificity. Here we revisited the effect of acute Foxp3+ Treg cell ablation on  cell autoimmunity in NOD mice in the context of a polyclonal TCR repertoire. For this, we took advantage of the well-established DTR/GFP transgene of DEREG mice, which allows for specific ablation of Foxp3+ Treg cells without promoting catastrophic autoimmune diseases. We show that the transient loss of Foxp3+ Treg cells in prediabetic NOD.DEREG mice is sufficient to precipitate severe insulitis and persistent hyperglycemia within 5 days after DT administration. Importantly, DT-treated NOD.DEREG mice preserved many clinical features of spontaneous diabetes progression in the NOD model, including a prominent role of diabetogenic CD8+ T cells in terminal  cell destruction. Despite the severity of destructive  cell autoimmunity, anti-CD3 mAb therapy of DT-treated mice interfered with the progression to overt diabetes, indicating that the novel NOD.DEREG model can be exploited for preclinical studies on T1D under experimental conditions of synchronized, advanced  cell autoimmunity. Overall, our studies highlight the continuous requirement of Foxp3+ Treg cell activity for the control of genetically pre-installed autoimmune diabetes.